Subjective well-being and relative poverty in rural Bangladesh - Niaz Asadullah; Nazmul Chaudhury (Institute for the Study of Labor (IZA), 2012)
This paper revisits the debate over the importance of absolute vs. relative income as a correlate of subjective well-being using data from Bangladesh, one of the poorest countries in the world with high levels of corruption and poor governance. We do so by combining household data with population census and village survey records. Our results show that conditional on own household income, respondents report higher satisfaction levels when they experience an increase in their income over the past years. More importantly, individuals who report their income to be lower than their neighbours in the village also report less satisfaction with life. At the same time, our evidence suggests that relative wealth effect is stronger for the rich. Similarly, in villages with higher inequality, individuals report less satisfaction with life. However, when compared to the effect of absolute income, these effects (i.e. relative income and local inequality) are modest. Amongst other factors, we study the influence of institutional quality. Institutional quality, measured in terms of confidence in police, matters for well-being: it enters with a positive and significant coefficient in the well-being function.
urn:nbn:de:101:1-201301213314
Keywords: O12; I30; I31; 330; poverty; well-being; institutions; Bangladesh; Zufriedenheit; Armut; Soziale Ungleichheit; Ländlicher Raum; Bangladesch